2012
DOI: 10.1371/journal.pone.0035568
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Epizootic Ulcerative Syndrome in Native Fish of the Murray-Darling River System, Australia: Hosts, Distribution and Possible Vectors

Abstract: Epizootic ulcerative syndrome (EUS) is a fish disease of international significance and reportable to the Office International des Epizootics. In June 2010, bony herring Nematalosa erebi, golden perch Macquaria ambigua, Murray cod Maccullochella peelii and spangled perch Leiopotherapon unicolor with severe ulcers were sampled from the Murray-Darling River System (MDRS) between Bourke and Brewarrina, New South Wales Australia. Histopathology and polymerase chain reaction identified the fungus-like oomycete Apha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…Initial outbreaks of disease in Africa (Andrew et al., ; Anon ; Huchzermeyer & Van der Waal, ; McHugh et al., ; Songe et al., ) have been particularly severe in floodplain ecosystems as observed during this study in the Bangweulu swamps where the initial severe outbreak of 2014 was followed by annual reappearance of the disease during the same months in 2015, 2016 and 2017 (personal observations C. F. Huchzermeyer, Bangweulu Wetlands, Chikuni, Zambia 2017). Following the initially severe epidemic, the seasonal resurgence of the disease observed in this study was similar to that reported during outbreaks of EUS in the upper Zambezi (Huchzermeyer & Van der Waal, ; Nsonga, Mfitilodze, Samui & Sikawa, ) and in other parts of the world (Boys et al., ; Pradhan et al., ). As with the initial outbreaks of EUS in the Zambezi floodplains, reported by Huchzermeyer and Van der Waal (), fishermen in the Bangweulu swamps soon accepted the presence of the disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Initial outbreaks of disease in Africa (Andrew et al., ; Anon ; Huchzermeyer & Van der Waal, ; McHugh et al., ; Songe et al., ) have been particularly severe in floodplain ecosystems as observed during this study in the Bangweulu swamps where the initial severe outbreak of 2014 was followed by annual reappearance of the disease during the same months in 2015, 2016 and 2017 (personal observations C. F. Huchzermeyer, Bangweulu Wetlands, Chikuni, Zambia 2017). Following the initially severe epidemic, the seasonal resurgence of the disease observed in this study was similar to that reported during outbreaks of EUS in the upper Zambezi (Huchzermeyer & Van der Waal, ; Nsonga, Mfitilodze, Samui & Sikawa, ) and in other parts of the world (Boys et al., ; Pradhan et al., ). As with the initial outbreaks of EUS in the Zambezi floodplains, reported by Huchzermeyer and Van der Waal (), fishermen in the Bangweulu swamps soon accepted the presence of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…Freshwater and estuarine ecosystems in tropical and subtropical climates are particularly vulnerable to outbreaks of EUS (Boys et al., ). Initial outbreaks of disease in Africa (Andrew et al., ; Anon ; Huchzermeyer & Van der Waal, ; McHugh et al., ; Songe et al., ) have been particularly severe in floodplain ecosystems as observed during this study in the Bangweulu swamps where the initial severe outbreak of 2014 was followed by annual reappearance of the disease during the same months in 2015, 2016 and 2017 (personal observations C. F. Huchzermeyer, Bangweulu Wetlands, Chikuni, Zambia 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The disease was first detected in Japan19, but has been subsequently reported from continental Asia, Australia, North America and Africa, with different names being given20. Based on several molecular studies, a single clone of A. invadans has been broadly distributed worldwide2122. A. astaci and A. invadans seem to be closely related on the genetic level5, and they also share several common life style characteristics; i.e.…”
mentioning
confidence: 99%
“…EUS has been reported in more than 94 fish species spread across 26 countries (Lilley et al, 1998;Andrew et al 2008;Saylor et al 2010;Boys et al 2012;Huchzermeyer et al 2012;Oidtmann, 2012). EUS was spread across Asia from Japan and Australia to Pakistan in 1996 and to southern Africa in 2006 (Baldock et al, 2005).…”
Section: Article May Be Cited Asmentioning
confidence: 99%